2017
DOI: 10.3748/wjg.v23.i22.4080
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the effect of targeted therapy of 64-slice spiral CT combined with cryoablation for liver cancer

Abstract: AIMTo observe the effect of targeted therapy with 64-slice spiral computed tomography (CT) combined with cryoablation for liver cancer.METHODSA total of 124 patients (142 tumors) were enrolled into this study. According to the use of dual-slice spiral CT or 64-slice spiral CT as a guide technology, patients were divided into two groups: dual-slice group (n = 56, 65 tumors) and 64-slice group (n = 8, 77 tumors). All patients were accepted and received targeted therapy by an argon-helium superconducting surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…CRA is associated with minimal trauma, significant therapeutic effects, and fewer postoperative complications, especially in the treatment of small liver cancer, which yields satisfactory results. Current research has shown that for early liver cancer patients with tumors < 3 cm, CRA ablation therapy can be an alternative to surgery[ 17 ]. However, the use of CRA for the treatment of liver cancer patients with lesions ≥ 5 cm has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…CRA is associated with minimal trauma, significant therapeutic effects, and fewer postoperative complications, especially in the treatment of small liver cancer, which yields satisfactory results. Current research has shown that for early liver cancer patients with tumors < 3 cm, CRA ablation therapy can be an alternative to surgery[ 17 ]. However, the use of CRA for the treatment of liver cancer patients with lesions ≥ 5 cm has limitations.…”
Section: Discussionmentioning
confidence: 99%
“… 54 The use of multi-slice spiral CT guidance to improve efficacy and reduce complications has been suggested in a study. 55 The use of MRI-CT fusion imaging to evaluate cryoablation margins in hepatocellular carcinoma has also been suggested. 56 Despite the lack of clinical studies on cryoablation of caudate lobe HCC, cryoablation has shown very good potential application for the treatment thereof.…”
Section: Percutaneous Ablationmentioning
confidence: 99%
“…The number of patients who die from LIHC each year exceeds half a million ( 4 ). In the early stages, LIHC has no symptoms but rapidly progresses ( 5 ). At present, LIHC is mainly treated with liver transplantation, hepatic resection, and medication ( 6 ).…”
Section: Introductionmentioning
confidence: 99%